2018
DOI: 10.24248/eahrj.v2i1.560
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Aetiological Agents, and Antimicrobial Sensitivity Pattern of Bacterial Meningitis Among Children Receiving Care at KCMC Referral Hospital in Tanzania

Abstract: Background: Bacterial meningitis is an inflammation of the meninges that occurs in response to bacteria, causing a significant number of morbidity and mortality worldwide, especially in newborns and people living in low-income countries. Diagnosis of bacterial meningitis combines a high index of clinical suspicion and laboratory confirmation through cerebrospinal fluid (CSF) analysis. Despite antibiotic treatment, mortality remains high and many children end with longterm consequences, which include neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…To ensure inherent paper quality appraisal, a 12-point scoring system based on the Downs and Black checklist was adapted for the current study [35,36]. Typically, these twelve items include the following: (1) if the research was clear about its objectives/aims/hypothesis, (2) if the research was clear about the study design it used, (3) if the study participants were representative, (4) whether the fnal recruits for the study were representative of the initial population (after some participants declined to participate), (5) if the study had a good sample size, (6) if the research stated incidence of missing data and how it was managed, (7) if the sociodemographic of participants were clearly stated, (8) if the association was quantifed, it controlled for confounders (9), whether the research very clear about the results it reported, (10) if the study was explicit about how the variable of interest was measured (diabetes and meningitis), (11) the study reported any potential cases of biases or acknowledged limitations if it existed, and (12) if the outcome of interest for the research was explicitly stated. Other items known to be associated with quality such as inclusion and exclusion criteria for recruiting eligible study subjects, were assessed.…”
Section: Data Extraction and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure inherent paper quality appraisal, a 12-point scoring system based on the Downs and Black checklist was adapted for the current study [35,36]. Typically, these twelve items include the following: (1) if the research was clear about its objectives/aims/hypothesis, (2) if the research was clear about the study design it used, (3) if the study participants were representative, (4) whether the fnal recruits for the study were representative of the initial population (after some participants declined to participate), (5) if the study had a good sample size, (6) if the research stated incidence of missing data and how it was managed, (7) if the sociodemographic of participants were clearly stated, (8) if the association was quantifed, it controlled for confounders (9), whether the research very clear about the results it reported, (10) if the study was explicit about how the variable of interest was measured (diabetes and meningitis), (11) the study reported any potential cases of biases or acknowledged limitations if it existed, and (12) if the outcome of interest for the research was explicitly stated. Other items known to be associated with quality such as inclusion and exclusion criteria for recruiting eligible study subjects, were assessed.…”
Section: Data Extraction and Qualitymentioning
confidence: 99%
“…Tis incident rate could be 10 times higher in resource-poor settings such as sub-Saharan Africa (SSA) and poorer countries in Asia [10]. For example, a study conducted in Tanzania reported a bacterial meningitis prevalence of 18.6% [11]. Typically, cryptococcal meningitis which is fungal-based has been discovered as the most prevalent among people living with HIV (PLHIV).…”
Section: Introductionmentioning
confidence: 99%
“…The associated clinical signs of bacterial meningitis include apnoea, fever, hypothermia, lethargy, seizures, bulging fontanel, nuchal rigidity, nausea, vomiting, coma, etc. However, the patient's age influences the clinical presentation of bacterial meningitis [9,10]. The diagnosis of the disease is generally a challenge in most health facilities because of the insufficient resources such as practitioners who can perform a lumbar puncture, appropriate equipment and access to microbiology; furthermore, bacterial meningitis causes fever.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patients suffer from the long term sequelae of the disease [7,8,10]. A study done in Tanzania on bacterial meningitis has reported a prevalence of 18.6% [9]. This calls for the improvement of the diagnostic facilities for early and effective diagnosis as well as early treatment to cater for risk factors for mortality in children under the age of ten years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation